2021
DOI: 10.1111/bjd.20436
|View full text |Cite
|
Sign up to set email alerts
|

A genome‐wide association study identifies novel gene associations with facial skin wrinkling and mole count in Latin Americans

Abstract: Background Genome-wide association studies (GWASs) have identified genes influencing skin ageing and mole count in Europeans, but little is known about the relevance of these (or other genes) in non-Europeans. Objectives To conduct a GWAS for facial skin ageing and mole count in adults < 40 years old, of mixed European, Native American and African ancestry, recruited in Latin America. Methods Skin ageing and mole count scores were obtained from facial photographs of over 6000 individuals. After quality control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 65 publications
1
18
0
Order By: Relevance
“…As previously reported in European skin, Chen et al 5 . confirm an association for skin wrinkling with polymorphisms in the IRF4 , MC1R and SLC45A2 genes – indicating their conserved nature.…”
supporting
confidence: 73%
See 1 more Smart Citation
“…As previously reported in European skin, Chen et al 5 . confirm an association for skin wrinkling with polymorphisms in the IRF4 , MC1R and SLC45A2 genes – indicating their conserved nature.…”
supporting
confidence: 73%
“…In this issue of the BJD , Chen et al 5 . describe the results of a large‐scale genome‐wide association study (GWAS) assessing features of facial skin ageing and mole count in Latin American adults of mixed European, Native American and African ancestry; that is, across the pigmentary continuum.…”
mentioning
confidence: 99%
“…These genetic variations identified in skin color genes contribute to facial pigmented spots during aging through pathways independent of the melanin production [58]. Recently, the association of variants in IRF4, MC1R, and SLC45A2 with skin wrinkling was confirmed in more ethnic groups [59]. The same study, using Latin Americans of a production [58].…”
Section: Skin Aging 21 Natural Process Of Skin Agingmentioning
confidence: 90%
“…The same study, using Latin Americans of a production [58]. Recently, the association of variants in IRF4, MC1R, and SLC45A2 with skin wrinkling was confirmed in more ethnic groups [59]. The same study, using Latin Americans of a mixed continental ancestry cohort, reported genetic variations in two new candidate genes, VAV3 and SLC30A1, associated with facial skin wrinkling and mole count, respectively [59].…”
Section: Skin Aging 21 Natural Process Of Skin Agingmentioning
confidence: 91%
See 1 more Smart Citation